Ocular hemodynamics in patients with rhegmatogenous retinal detachment complicated by choroidal detachment (Ukrainian Journal of Ophthalmology, 2025)
Background: The occurrence of choroidal detachment (CD) in eyes with primary rhegmatogenous retinal detachment (RRD) is relatively uncommon (2%-8.6%). We hypothesized that significant disturbances in blood supply to the retina are a mechanism of the pathogenesis of RRD complicated by CD, which prompted us to study ocular hemodynamics in relevant patients.Purpose: To assess preoperative hemodynamics of the affected eye and fellow eye in patients with RRD complicated by CD.Material and Methods: We preoperatively examined the affected eye and fellow eye and assessed their hemodynamics in two groups of 11 patients each (the uncomplicated RRD group and the RRD complicated by CD group) which were similar with regard to age, time from the onset of RRD and ocular comorbidity.Results: Volumetric ocular pulse blood filling (OPBF) values in the affected eye and fellow eye of the latter group were 68.7% and 40%, respectively, lower, whereas of the former group, 33.3% and 27%, respectively, lower, than in age-matched normals. In addition, volumetric ocular pulse blood filling positively correlated with intraocular pressure (r=0.5; p < 0.05) in patients of both groups. This indicated that there is a significant ischemic process in the eye with RRD, which is aggravated in the presence of CD.
Keywords: rhegmatogenous retinal detachment; choroidal detachment; ophthalmic rheography; ocular pulse blood filling; intraocular pressure